Carbon shock : a tale of risk and calculus on the front lines of the disrupted global economy, how carbon is changing the cost of everything - Schapiro, Mark, 1955- (White River Junction : Chelsea Green Publishing, 2014)
In Carbon Shock, veteran journalist Mark Schapiro takes readers on a journey into a world where the same chaotic forces reshaping our natural world are also transforming the economy, playing havoc with corporate calculations, shifting economic and political power, and upending our understanding of the real risks, costs, and possibilities of what lies ahead. In this ever-changing world, carbon--the stand-in for all greenhouse gases--rules, and disrupts, and calls upon us to seek new ways to reduce it while factoring it into nearly every long-term financial plan we have. But how? From the jungles of the Amazon to the farms in California's Central Valley, from 'greening' cities like Pittsburgh to rising powerhouses like China, from the oil-splattered beaches of Spain to carbon-trading desks in London, Schapiro deftly explores the key axis points of change. For almost two decades, global climate talks have focused on how to make polluters pay for the carbon they emit. It remains an unfolding financial mystery: What are the costs? Who will pay for them? Who do you pay? How do you pay? And what are the potential impacts? The answers to these questions, and more, are crucial to understanding, if not shaping, the coming decade. Carbon Shock evokes a world in which the parameters of our understanding are shifting--on a scale even more monumental than how the digital revolution transformed financial decision-making--toward a slow but steady acknowledgement of the costs and consequences of climate change. It also offers a critical new perspective as global leaders gear up for the next round of climate talks in 2015.
Dogfight over my flight : airplanes -- Eat, drink, pray : food : the front line -- Earth, wind, and heat : food : our liability -- The forest for its carbon : the tree -- Carbon in the tank : oil -- A tale of three cities : the city -- The clean dark spread : pricing carbon -- Trading in hot air : stealing carbon -- The coffee and the cup : shuffling the decks in the new carbon economy.
Includes bibliographical references (pages 191-204) and index.
Keywords: Environmental economics; Energy industries -- Environmental aspects; Economic policy -- Environmental aspects; Carbon dioxide mitigation; BUSINESS & ECONOMICS -- Environmental Economics; POLITICAL SCIENCE -- Public Policy -- Economic Policy; BUSINESS & ECONOMICS -- Industries -- Energy Industries; TECHNOLOGY & ENGINEERING -- Power Resources -- Fossil Fuels; BUSINESS & ECONOMICS -- International -- Economics; Economie de l'environnement.; Energie; Dioxyde de carbone; Effets sur l'environnement.; Carbon dioxide mitigation; Economic policy -- Environmental aspects; Energy industries -- Environmental aspects; Environmental economics; Kohlendioxidemission; Umweltschutz